Mediation Implementation in Inheritance Dispute Resolution: A Study of The Sibuhuan Religious Court Under Supreme Court Regulation No. 1 of 2016 - Akmal Marzuki Daulay; Muhlizar; Zuhri Arif (Inovasi Pratama Internasional. Ltd, 2027)
This study examines the implementation of mediation in resolving inheritance disputes at the Sibuhuan Religious Court under Supreme Court Regulation (PERMA) No. 1 of 2016 concerning Court Mediation Procedures. Inheritance disputes frequently arise in Indonesian Muslim communities due to disagreements over inheritance distribution, often leading to prolonged family conflicts. This research employs an empirical juridical method with a qualitative case study approach, utilizing data collection techniques including interviews, observation, and documentation studies. The findings reveal that mediation implementation at the Sibuhuan Religious Court has generally complied with PERMA No. 1 of 2016 procedural requirements, with supporting factors including the availability of certified mediator judges, adequate mediation facilities, and cultural values promoting family harmony. However, inhibiting factors significantly constrain success rates, including low legal awareness among parties, sharp interest conflicts, limited mediation timeframes, and communication barriers such as language differences. The success rate of mediation in inheritance disputes at the Sibuhuan Religious Court ranges between 40%–50%, indicating its effectiveness as a dispute resolution mechanism while demonstrating considerable room for improvement. This research contributes to understanding the practical challenges of court-annexed mediation in religious court settings and offers recommendations for enhancing mediation effectiveness through improved mediator training, expanded public legal education, and strengthened procedural enforcement mechanisms. The study concludes that mediation remains a valuable alternative to full litigation, offering faster, more cost-effective, and relationship-preserving outcomes when properly implemented